Strategic solutions to employee turnover in the animal health industry - McWherter, Megan Kay (Kansas State University, 2021)
Employee turnover is very expensive for organizations. When it is an industry-wide challenge, then it demands a careful assessment for insights into the antecedents to the problem and an effective strategic response to it. There are many theories that consider motivations for employee turnover. However, there is no research to understand the high turnover in the veterinary profession. The purpose of this thesis is to examine the motivation of high employee turnover in the animal health industry. The research question that the research attempts to answer is this: What are the characteristics of employees and the workplace that motivate their decisions to exit the industry? The overall research objective was to explore employee characteristics and work environment that influenced their retention decisions. The study used survey data collected using the Qualtrics platform. The collection period was about four weeks. The diversity in the number of respondents did not allow the estimation of the original logistic regression methods to answer the question. As a result, the study employed a statistical approach. The results indicate that the correlation between employees who say they find their work environment to be stressful and feeling unmotivated to go to work in the morning was 0.39 (p < 0.001). Those feeling burnout was more likely to be those who are feeling compassion fatigue (r = 0.42; p < 0.001) and those feeling burnout are likely to feel unmotivated to go to work (r = 0.65; p < 0.001). The results also indicated that perceptions of uncompetitive compensation and an unfriendly or unsupportive work environment were viewed as factors motivating the risk of quitting by just under 50% of respondents while about a third said these were not factors influencing their risk of quitting. The research results begin to provide some indications in how the veterinary industry may modify the management of its staff to minimize employee turnover risks. They suggest recognizing the effect of workload on burnout and compassion fatigue and structuring work to give employees time to recuperate from the high emotional environment in which they work. The results show that this is true for all types of employees, including front office staff, who are often the ones dealing with clients and handling most of the emotional dimensions of the engagement.
Keywords: Animal health; Veterinary practice; Employee retention; Compassion fatigue; Management